Extended Sequential Function Chart - Leslaw Gniewek; Michal Markiewicz (IEEE Access)
Sequential Function Chart (SFC) is one of the PLC programming languages defined in the IEC-61131 standard. SFC has been increasingly used in practical applications because even small controllers can now be programmed in this graphical language. Representing the sequential-parallel control algorithm in the form of a diagram makes the program transparent, and the possibility of using Petri net analysis tools allows for formal verification of the program’s correctness. Unfortunately, in SFC, the graph nodes take only binary values, which limits, for example, the possibility of modeling resources that are produced or consumed during the production process. It also makes the use of signals from analog sensors challenging, thanks to which it is possible to observe the progress of the supervised tasks. Hence, this paper proposes an extension of SFC (eSFC), which introduces nodes that model quantitative resources and variables storing analog signals. In addition, a formal model of eSFC and its algebraic interpretation are proposed, ensuring the unambiguity of the eSFC operation.